REMOVAL OF FLUORIDE USING NEEM LEAVES BATCH REACTOR: KINETICS AND EQUILIBRIUM STUDIES - Singh, Tej Pratap; Cb, Majumder (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this paper is to study the fluoride removal efficiency of the neem leaves low-cost biosorbent for defluoridation of sewage wastewater. Methods: For finding the best operating condition for maximum removal of fluoride, batchwise experiments were performed at different contact times and keeping other parameters to be constant such as pH, initial fluoride concentration, and adsorbent dose. Various kinetic models such as intraparticle diffusion model, Bangham's model, and Elovich model had been investigated for determining the suitable adsorption mechanism. The rate of adsorption of fluoride on neem leaves has been determined by pseudo-first-order and pseudo-second-order rate models. Results: The adsorption kinetics rate and mechanism was best described by the pseudo-second-order model and Bangham's model, respectively. The optimum pH, initial concentration, adsorbent dose, and contact time were found to be 7, 20 mg/L, 10 g/L, and 40 min, respectively, for which there was maximum fluoride removal. Conclusion: The result obtained from the experiments show that the neem leaves have been proved to be a low-cost biosorbent for the defluoridation of the sewage wastewater and have high fluoride removal efficiency.